2020
DOI: 10.1111/sltb.12623
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Minority Stress Theory and the Interpersonal Theory of Suicide among Sexual Minority Youth Who Engage Crisis Services

Abstract: ObjectiveThe present study sought to integrate minority stress theory (MST) and the interpersonal theory of suicide (ITS) to better understand high rates of suicide among sexual minority youth (SMY). To date, the ITS and MST have largely advanced independently from one another even though the research base for each theory contains gaps that the other theory may help fill.MethodUsing data from a national sample of 564 SMY (aged 12–24) recruited from an LGBTQ youth‐focused suicide crisis prevention provider, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 53 publications
5
49
0
Order By: Relevance
“…It is difficult to understand these findings in the absence of a more thorough and detailed investigation of potential mechanisms for these effects. There is a growing literature using minority stress theory to understand suicide risk [53,54]. In the interpersonal violence field, experiencing victimization (which occurs disproportionately among some groups) is related to greater helping [55].…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to understand these findings in the absence of a more thorough and detailed investigation of potential mechanisms for these effects. There is a growing literature using minority stress theory to understand suicide risk [53,54]. In the interpersonal violence field, experiencing victimization (which occurs disproportionately among some groups) is related to greater helping [55].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are few empirically identified psychological mechanisms linking homophobic discrimination and violence to suicidal ideation for sexual minority people (Hatzenbuehler, 2009;Plöderl et al, 2013Plöderl et al, , 2014 that are guided through integrating explanatory theories of suicide with the minority stress framework (e.g., Baams et al, 2015;Fulginiti et al, 2020;Hill & Pettit, 2012). Both Baams et al (2015) and Hill and Pettit (2012) tested constructs from the interpersonal psychological theory of suicide (IPTS; Joiner, 2005) and reported that experiences of minority stress were associated with suicidal ideation through perceived burdensomeness (e.g., perceptions that one is a drain on others' resources or perceiving that others would be "better off without me") but not through thwarted belongingness (e.g., perceptions of not being supported by, and connected to others) (Joiner, 2005;van Orden et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the few pioneering studies (e.g., Baams, Grossman, & Russell, 2015;Fulginiti et al, 2020;Hill & Pettit, 2012;Li et al, 2016) that have integrated the minority stress framework with theoretical models of suicide suggest that various forms of minority stress, entrapment, and social belongingness are critical factors that may be interrelated for understanding suicidal ideation in sexual minority emerging adults. These existing studies, however, do not offer empirical support for social belongingness as an independent mediating factor between minority stress and suicidal ideation and behaviors (e.g., Baams et al, 2015;Cramer, Burks, Stroud, Bryson, & Graham, 2015;Fulginiti et al, 2020;Hill & Pettit, 2012). We expand on this current body work by considering that the propensity to engage in suicidal ideation when experiencing homophobic violence may be explained through feeling entrapped; and these associations may be enhanced (moderated) when social belongingness scarce (O'Connor & Nock, 2014).…”
Section: The Current Studymentioning
confidence: 99%
“…Numerous cross-sectional studies have attributed health outcomes among adolescents to minority stressors including negative disclosure experiences with family and peers (Haas et al, 2010 ; McGeough and Sterzing, 2018 ; Poštuvan et al, 2019 ; Gamarel et al, 2020 ), homelessness (Rice and Barman-Adhikari, 2014 ; Tyler and Ray, 2019 ), perceived burdensomeness (Baams et al, 2018 ; Fulginiti et al, 2020 ) in-school victimization (bullying) by students and faculty members (Toomey et al, 2013 ; Norris and Orchowski, 2020 ), and experiences of violence (Kosciw et al, 2012 ; Sterzing et al, 2017 ; Schwab-Reese et al, 2021 ). Fear of rejection from family may also lead SMA to not disclose their identity to parents (Padilla et al, 2010 ), and lack of family support is often cited as a precursor to SMA homelessness (e.g., Ryan et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with minority stress theory, the measure includes subscales that represent both proximal and distal stressors. Emerging evidence suggests the SMASI may have utility for understanding behavioral health outcomes in both general population (e.g., Goldbach et al, 2017b ) and clinical (e.g., Fulginiti et al, 2020 ) samples. However, the reliability and validity of this measure have not been established in a large national sample, and questions remain about the generalizability of previous findings to broader populations of sexual minority youth.…”
Section: Introductionmentioning
confidence: 99%